2011
DOI: 10.1158/1055-9965.epi-11-0766
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Cohort Study of Coffee Consumption and Risk of Endometrial Cancer over a 26-Year Follow-Up

Abstract: Background Coffee has been reported to lower levels of estrogen and insulin, two hormones implicated in endometrial carcinogenesis, but prospective data on the relation between coffee consumption and risk of endometrial cancer are limited. Methods We prospectively assessed coffee consumption in relation to endometrial cancer risk in the Nurses’ Health Study (NHS) with 67,470 female participants aged 34–59 in 1980. Cumulative average coffee intake was calculated with all available questionnaires to assess lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 47 publications
(50 reference statements)
3
49
0
1
Order By: Relevance
“…Consistent with our results, four recent studies found an inverse association of coffee with EC, particularly among women with BMI ⩾30 kg m −2 (Friberg et al , 2009; Giri et al , 2011; Gunter et al , 2011; Je et al , 2011). For the first time, we extend this association specifically to Type I EC and to coffee but not other common sources of methylxanthines, which were not addressed by these prior studies.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with our results, four recent studies found an inverse association of coffee with EC, particularly among women with BMI ⩾30 kg m −2 (Friberg et al , 2009; Giri et al , 2011; Gunter et al , 2011; Je et al , 2011). For the first time, we extend this association specifically to Type I EC and to coffee but not other common sources of methylxanthines, which were not addressed by these prior studies.…”
Section: Discussionsupporting
confidence: 93%
“…The inverse association between coffee intake and EC risk is consistent with two recent meta-analyses (3, 13) and an earlier NHS report (14). Obesity is a strong risk factor for EC (2) and may act by increasing exposure to estrogen (15) and/or hyperinsulinemia (16).…”
Section: Discussionsupporting
confidence: 90%
“…Increasing consumption of caffeine and caffeine-containing coffee was associated with higher levels of adiponectin in the NHS which may benefit insulin sensitivity (18), and also with elevated levels of sex hormone-binding globulin (SHBG) that may decrease bioavailable estrogen based on a report focusing on postmenopausal women in the Rancho Bernardo community-based study (19). However, epidemiologic evidence suggests that non-caffeine components of coffee may be important for the risk reduction based on observations in the WCRF meta-analysis (3) that the decreased risk for EC is similar in magnitude for decaffeinated coffee, and because drinking tea which also contains caffeine does not appear to be related to EC risk in the current study and in the earlier NHS report (14) and WCRF meta-analysis (3). …”
Section: Discussionmentioning
confidence: 44%
“…It contains over 1000 chemical compounds, many of which, including caffeine, diterpenes, and phenolic acids, are known to be bioactive. 1 Strong inverse associations of coffee drinking with liver cancer 2 and endometrial cancer 3, 4 have been consistently observed. However, evidence of an association with other cancers, including breast, 5 prostate, 6 and lung 7 is less consistent.…”
Section: Introductionmentioning
confidence: 96%